Non-Invasive Multiphoton Imaging of Islets Transplanted Into the Pinna of the NOD Mouse Ear Reveals the Immediate Effect of Anti-CD3 Treatment in Autoimmune Diabetes - Benson, Robert A.; Garcon, Fabien; Recino, Asha; Ferdinand, John R.; Clatworthy, Menna R.; Waldmann, Herman; Brewer, James M.; Okkenhaug, Klaus; Cooke, Anne; Garside, Paul; Wållberg, Maja (Frontiers in Immunology, 2018)
We present a novel and readily accessible method facilitating cellular time-resolved imaging for investigation of immune processes, beta cell development, differentiation and function in the development and treatment of autoimmune diabetes. Grafting of islets to the mouse ear pinna allows non-invasive, in vivo longitudinal imaging of events in the islets and enables improved acquisition of experimental data and use of fewer experimental animals than is possible using invasive techniques, as the same mouse can be assessed for presence of islet infiltrating cells before and after immune intervention. We have applied this method to investigating therapeutic protection of beta cells through the well-established use of anti-CD3 injection, and have acquired unprecedented data on the nature and rapidity of the effect on the islet infiltrating T cells. We demonstrate that infusion of anti-CD3 antibody leads to immediate effects on islet infiltrating T cells in islet grafts in the pinna of the ear, and causes them to increase their speed and displacement within 20 minutes of infusion. This technique overcomes several technical challenges associated with intravital imaging of pancreatic immune responses and facilitates routine study of beta islet cell development, differentiation and function in health and disease.